A Critical Review: A Significant Role of Women in the Development of the Society - Brohi, Sidra Ismail; Mirani, Jawaid Iqbal; Jarah, Ayaz Ali; Brohi, Shair Ali (International Journal of Culture and History, 2024)
Women are equal to men in Pakistan and contribute with some effort to economic development, democratic stability, and social quality. It is fact that Pakistani society is male-dominated and male constitutes a major part of the population of the country. In this regard, women face many problems to progress and obtain due status. In spite of all hurdles, Pakistani women are being an important contribution to the development of society in both rural and urban areas of all provinces. This paper discusses different roles of women from an Islamic point of view, roles of women in the Labour Force, and roles of women in the politics of Pakistan. The explanatory method has been for data collection from the secondary sources data collection like research articles, research journal and books. The finding of the article indicates that women despite numerous difficulties they are motivated, industrious and ready to work for the progress of the society of Pakistan. Consequently, the government and competent authorities should focus on the education, health, nutrition, training, safety and freedom of Pakistani women so that they can play their roles in the development of the country without any fear and discrimination.